2017
DOI: 10.1124/mol.116.106781
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of a De Novo GRIN2A Mutation Identified in a Patient with Profound Global Developmental Delay and Refractory Epilepsy

Abstract: The N-methyl-d-aspartate receptor (NMDAR), a ligand-gated ionotropic glutamate receptor, plays important roles in normal brain development and a wide range of neurologic disorders, including epilepsy. Here, we evaluate for the first time the functional properties of a de novo missense mutation (p.M817V) in the pre-M4 linker in a child with profound global developmental delay and refractory epilepsy. Electrophysiologic recordings revealed that the mutant GluN2A(M817V)-containing receptors showed enhanced agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 76 publications
0
110
0
Order By: Relevance
“…Electrophysiological studies have shown significant impairment in channel gating properties by mutations in these positions (Chen et al, 2017; Ogden et al, 2017). Moreover, the external half of the M4 helix, partly via intrasubunit interactions with the membrane-parallel pre-M1 helix, contributes significantly to channel activation (Amin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological studies have shown significant impairment in channel gating properties by mutations in these positions (Chen et al, 2017; Ogden et al, 2017). Moreover, the external half of the M4 helix, partly via intrasubunit interactions with the membrane-parallel pre-M1 helix, contributes significantly to channel activation (Amin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…(Zhou and Cross, 2013). The lack of an open state structure has greatly hampered mechanistic understanding of iGluRs (Amin et al, 2017; Chen et al, 2017; Ogden et al, 2017; Zhou and Wollmuth, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The whole‐cell voltage clamp current recordings were performed on transiently transfected human embryonic kidney cells 293 (HEK293) (ATCC CRL‐1573, Manassas, Virginia) with plasmid cDNAs encoding WT human GluN1/GluN2A or GluN1/GluN2A‐A643D with a solution containing (in mM) 150 NaCl, 3 KCl, 10 HEPES (4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid), 0.01 EDTA, 1.0 CaCl 2 (calcium chloride), and 11 D‐mannitol, with the pH adjusted to 7.4 by the addition of NaOH (sodium hydroxide) (23 °C) . The recording electrodes were prepared a vertical puller (Narishige P‐10, Tokyo, Japan) using thin‐walled filamented borosilicate glass (TW150F‐4; World Precision Instruments, Sarasota, Florida) and filled with the internal solution (in mM: 110 D‐gluconic acid, 110 CsOH (cesium hydroxide), 30 CsCl (cesium chloride), 5 HEPES, 4 NaCl, 0.5 CaCl 2 , 2 MgCl 2 , (magnesium chloride) 5 BAPTA (1,2‐bis(o‐aminophenoxy)ethane‐N,N,Nâ€Č,Nâ€Č‐tetraacetic acid), 2 Na 2 ATP (adenosine 5â€Č‐triphosphate disodium), 0.3 NaGTP (guanosine 5â€Č‐triphosphate sodium); pH 7.35 with 300‐310 mOsmol/kg of the osmolality).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Carvill and colleagues identified GRIN2A mutations in 9% (4/44) of patients with epilepsy‐aphasia spectrum. Alterations in GRIN2A have also been reported in patients with early‐onset epileptic encephalopathy and severe developmental delay . To date, whole‐exome and genome sequencing have identified a substantial number of point mutations and deletions (>100) scattered across all domains of the GRIN2A gene .…”
mentioning
confidence: 99%
“…In the NMDAR M4 segments, there are numerous missense mutations associated with clinical pathologies (Figures 1b & 1c; Supplementary Table 1). These mutations are primarily located in the extreme extracellular third of the M4 segments (Figure 1c), which participates strongly in ion channel gating 15,16 , implicating gating deficits as a potential cause for these disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%